Small Investment, Big Impact: Engineering Economics Study on Early Childhood Education Infrastructure in the Era of Sustainable Development - Adela Anita; Hermanto Tinambunan; Andriani Effendi; Gabriel Gloria Ohee (Indo Publishing, 2025)
Early Childhood Education is the main foundation in shaping the quality of human resources in the future. However, investment in Early Childhood Education infrastructure is still considered a cost burden, not a strategic opportunity. This study aims to examine in depth the technical economic values of Early Childhood Education infrastructure development amidst the demands of sustainable development. This research uses a descriptive-qualitative case study approach and technical economic feasibility analysis methods in the form of Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Benefit-Cost Ratio (BCR). The results show that the development of Early Childhood Education infrastructure in the study area has a positive NPV, an IRR higher than the discount rate, and a PP below the building's operational period. In addition, a BCR value > 1 indicates that the investment is feasible and has a broad impact. These findings prove that small investments in Early Childhood Education infrastructure not only produce long-term social impacts but also provide tangible economic value. Therefore, the integration of technical economic principles in Early Childhood Education development policies needs to be a priority to address the challenge of poverty in basic education in Indonesia. This study strengthens the argument that education is not simply a social expenditure, but also a long-term investment that provides tangible returns for society and the country.